Analisis Sistem Absensi Berbasis Mobile Menggunakan Face Recognition pada Lingkungan Kantor Kota Tangerang - Agus Budiman; Agus Apri Hidayat; Pramudya Adi Saputra; Samso Supriyatna (CV. Shofanah Media Berkah, 2025)
The development of information technology has encouraged government agencies to adopt digital systems in various administrative aspects, including employee attendance management. The implementation of this digital system aims to improve the effectiveness, accuracy, and transparency of attendance recording. This study aims to analyze the implementation of a mobile-based attendance system integrated with facial recognition technology in the Tangerang City Office environment. The research method used is descriptive qualitative with data collection techniques through literature studies, observation, and documentation. The results show that the use of facial recognition technology can improve the accuracy of attendance recording, strengthen data security, and reduce the potential for fraud. However, the implemented system still has limitations, particularly related to environmental lighting conditions and the quality of the supporting devices used.